Population structure analysis and molecular characterization of duckweed genotypes using ipbs and issr markers - Coskun, Omer Faruk; Aydin, Didem (Bangladesh Journal of Botany, 2024)
The duckweed subfamily, Lemnoideae, is the smallest group of flowering plants. It is considered a vegetable since duckweeds are used for human nutrition, and there are species in this plant group with high potential for minor vegetables. Genetic diversity and molecular characterization of duckweed genotypes grown in different ecosystems were determined in this study. Using ISSR (Inter Simple Sequence Repeats) and iPBS (Inter-Primer Binding Site) markers, 67 genotypes of five duckweed species were characterized. ISSR and iPBS methods identified 100% polymorphism, with genetic similarity coefficients between Spirodela and Lemna species ranging from 0.17 to 0.56. Structure analysis conducted according to K=6 calculation revealed that L. minor species had the most homogeneous and diverse populations. Duckweed genotypes and species displayed a wide range of genetic diversity. Using various marker techniques, we determined the genetic structure of duckweed and characterized it as an alternative cheap, sustainable, and cheap source of protein, vegetables, and biofuel. As a result of this study, data obtained from duckweed genotypes will be useful for understanding molecular mechanisms in future genetic improvements of duckweed species. Bangladesh J. Bot. 53(4): 871-880, 2024 (December)